Electronic and computer music - Manning, Peter 1948- (Oxford Oxford University Press, 2004)
This book offers a distinctly sociolinguistic perspective on the nature of language in digital technologies. It starts by bringing new media sociolinguistics up to date, addressing technologies like instant messaging, text messaging, blogging, photo-sharing, mobile phones, gaming, social network sites, and video sharing. Chapters cover a range of communicative contexts (journalism, tourism, leisure, performance, public debate), communicators (professional and lay, young people and adults, intimates, and groups), and languages (Irish, Hebrew, Chinese, Finnish, Japanese, German, Greek, Arabic, French, and English). The volume is organized around topics of primary interest to sociolinguists and discourse analysts, including genre, style, stance, language ideology, and multimodality.
Electronic reproduction.
Keywords: Electronic music -- History and criticism; Computer music -- History and criticism; Electronic books